Sustainable innitiatives taken by p&g to protect environment - Kumar, Ashish; Gautam, Arpit; Yadav, Seeta Ram; Grag, Radhesh (Recent Research in Science and Technology, 2014)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> In the era of rapid industrialization and fast-track development the environmental issues suffer a lot. Be it any industry, organization or society the development must be carried out keeping the sustainability in mind. The opportunity of these overnight development approaches has ramified the environmental issues. The present communication enumerates the measures of environmental impact by taking a case of Procter and Gamble. Authors have studied the strategies of Procter and Gamble and their sustainable behavior in Indian as well as global context. Various data of last decade has been analyzed. It is found that the company P&G is moving in a right direction by providing new paradigms of realistic development. All the data for this study has been taken from secondary sources. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>